Effect of en bloc ovariohysterectomy on Thl/Th2 cytokine balance and organ histopathology in rats - Risvanli, Ali; Timurkaan, Necati; Saat, Nevzat; Dogan, Halef; Seker, Ibrahim (Polish Soc Veterinary Sciences Editorial Office, 2017)
The aim of this study was to investigate the effects of en bloc ovariohysterectomy on the Thl/Th2 cytokine balance, as well as on visceral organ and brain histopathology in rats. A total of 28 Sprague Dawley female rats aged 3-4 months and weighing 200-250 grams were used in the study. Fourteen of them were pregnant. The 14 non-pregnant rats were divided into two groups: the control group (Group 1, n: 7) and the ovariohysterectomized group (Group 2, n: 7). All rats underwent en bloc ovariohysterectomy on gestational day 20-21. The 14 pregnant rats were divided into two groups: those with live infants were grouped as Group 3 and those with dead infants were grouped as Group 4. All the rats (n: 28) were decapitated at the end of one month, blood samples were obtained, and the organs were isolated. The Thl [interleukin 2 (IL-2), tumor necrosis factor alpha (TNF alpha)] and Th2 [interleukin 4 (IL-4), and interleukin 10 (IL-10)] levels in the blood sera were measured by the ELISA method, and histopathological analysis was performed on the isolated tissues. The differences between the groups were found to be insignificant with regard to IL-2, IL-4, and TNF alpha levels (p > 0.05). However, a significant difference was observed for IL-10 levels between Groups 3 and 4 (p < 0.05), and the highest IL-10 level (150.32 +/- 71.64 pg/ml) was determined in Group 4. No important pathological findings were observed in the cardiac and brain tissues of any of the animals in the histopathological examination. Inflammatory changes were observed in the pulmonary and renal tissues of the rats in Groups 2, 3, and 4, where the changes were commonly interstitial pneumonia in Groups 2 and 4, and interstitial nephritis in Group 3. According to the findings of this study, en bloc and standard ovariohysterectomies performed in rats had similar effects on the Thl/Th2 cytokine balance and the histopathology of the brain and visceral organs.
Keywords: en bloc ovariohysterectomy; Thl/Th2 cytokine; histopathology; rats